Nutrition and Vascular Supply of Retinal Ganglion Cells during Human Development - Rutkowski, Paul; May, Christian Albrecht (Frontiers in Neurology, 2016)
Purpose. To review the roles of the different vascular beds nourishing the inner retina (retinal ganglion cells) during normal development of the human eye and using our own tissue specimens to support our conclusions. Methods. An extensive search of the appropriate literature included PubMed, Google scholar, and numerous available textbooks. In addition, choroidal and retinal NADPH-diaphorase stained whole mount preparations were investigated. Results. The first critical interaction between vascular bed and retinal ganglion cell (RGC) formation occurs in the 6th-8th month of gestation leading to a massive reduction of RGCs mainly in the peripheral retina. The first three years of age are characterized by an intense growth of the eyeball to near adult size. In the adult eye, the influence of the choroid on inner retinal nutrition was determined by examining the peripheral retinal watershed zones in more detail. Conclusion. This delicately balanced situation of retinal ganglion cell nutrition is described in the different regions of the eye, and a new graphic presentation is introduced to combine morphological measurements and clinical visual field data.